2020
DOI: 10.1002/jum.15386
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler Ultrasound in Portal Hypertension

Abstract: Portal hypertension is one of the most important causes of morbidity and mortality in cirrhotic patients. A color Doppler evaluation of the left gastric vein (LGV) has proven utility in the prediction of esophageal varices and variceal bleeding in patients with portal hypertension. The purpose of this review is to discuss the ultrasound evaluation, imaging findings, and clinical application of Doppler ultrasound in the assessment of the LGV. Knowledge of the color Doppler technique and imaging findings of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Hemodynamic changes in the left gastric vein during liver cirrhosis play a crucial role in predicting the risk of EVB. 16 Our results showed that LGVI in the EVB group was higher than that in the non-EVB group, and the risk of EVB would increase when the left gastric venous blood flow increased.…”
Section: Discussionmentioning
confidence: 50%
“…Hemodynamic changes in the left gastric vein during liver cirrhosis play a crucial role in predicting the risk of EVB. 16 Our results showed that LGVI in the EVB group was higher than that in the non-EVB group, and the risk of EVB would increase when the left gastric venous blood flow increased.…”
Section: Discussionmentioning
confidence: 50%
“…[10] It offers several advantages, including minimal trauma, no radiation exposure, quick and convenient operation, and widespread utilization in clinical practice. [11] It can be used for examination of the brain, [12] liver, [13] spleen, [14] stomach, [15] kidney, [16] breast [17] and uterus, [18] along with screening for vascular diseases, especially cardiovascular diseases. [19] Color Doppler can be conveniently and accurately applied in the screening of fetal heart malformations during pregnancy, which can clearly diagnose and reduce the birth rate of newborns with congenital heart disease.…”
Section: Ethics Approval Was Not Required Because This Review Contain...mentioning
confidence: 99%
“…The quality of the enrolled studies was assessed using the Cochrane Center Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2). Guohuai Zhang [11] 2019 China 47/1433 Color Doppler 47 1 2 1433 96 (86,100) 100 (100, 100) Haijing Fan [12] 2020 China 20/234 Color Doppler 20 1 1 234 95 (76,100) 100 (98, 100) Haohan Li [13] 2015 China 74/2926 Color Doppler 74 8 4 2926 95 (87, 99) 100 (99,100) Jing Chen [14] 2020…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation